Development of Siap Antisipasi (SIANTI) to Enhance Students’ Assertive Behavior in Preventing Physical Sexual Harassment on Junior High School Students - Ratnasari, Fitri; Flurentin, Elia; Setiyowati, Arbin Janu (Jurnal Kajian Bimbingan dan Konseling, 2022)
This research and development aims to develop a product called Siap Antisipasi (SIANTI) to improve assertive behavior in preventing physical sexual harassment in junior high school students by meeting product acceptance. SIANTI’s products include three educational videos with a video duration of three minutes each and a guidebook for school counselors in providing classical guidance services. The research method by adapting Borg and Gall model. This research and development procedure includes preliminary studies, product design and development as well as product testing of material experts, media experts and users. The research and development subjects consisted of one material expert, one media expert and two users. Assessment of expert and users to determine product acceptance uses a rating scale based on aspects of accuracy, usability, convenience and product attractiveness. The research instrument uses an expert and prospective user assessment format. The results of the expert test were analyzed using the numerical average, the results of the users were tested using the inter-rater agreement. The overall test results show that the SIANTI product gets a very high rating category and meets product acceptance so that it can be implemented as a medium for school counselors in providing classical guidance services to improve students’ assertive behavior to prevent physical sexual harassment.